National Antibiotics Utilization Trends for Human Use in Tanzania from 2010 to 2016 Inferred from Tanzania Medicines and Medical Devices Authority Importation Data - Raphael Zozimus Sangeda; Habibu Ally Saburi; Faustine Cassian Masatu; Beatrice Godwin Aiko; Erick Alexander Mboya; Sonia Mkumbwa; Adonis Bitegeko; Yonah Hebron Mwalwisi; Emmanuel Alphonse Nkiligi; Mhina Chambuso; Hiiti Baran Sillo; Adam M. Fimbo; et al. (MDPI AG, 2021)
Antimicrobial use (AMU) is one of the major drivers of emerging antimicrobial resistance (AMR). The surveillance of AMU, which is a pillar of AMR stewardship (AMS), helps devise strategies to mitigate AMR. This descriptive, longitudinal retrospective study quantified the trends in human antibiotics utilization between 2010 and 2016 using data on all antibiotics imported for systemic human use into Tanzania's mainland. Regression and time series analyses were used to establish trends in antibiotics use. A total of 12,073 records for antibiotics were retrieved, totaling 154.51 Defined Daily Doses per 1000 inhabitants per day (DID), with a mean (±standard deviation) of 22.07 (±48.85) DID. The private sector contributed 93.76% of utilized antibiotics. The top-ranking antibiotics were amoxicillin, metronidazole, tetracycline, ciprofloxacin, and cefalexin. The DIDs and percentage contribution of these antibiotics were 53.78 (34.81%), 23.86 (15.44), 20.53 (13.29), 9.27 (6.0) and 6.94 (4.49), respectively. The time series model predicted a significant increase in utilization (p-value = 0.002). The model forecasted that by 2022, the total antibiotics consumed would be 89.6 DIDs, which is a 13-fold increase compared to 2010. Government intervention to curb inappropriate antibiotics utilization and mitigate the rising threat of antibiotic resistance should focus on implementing AMS programs in pharmacies and hospitals in Tanzania.